2019
DOI: 10.1108/jcm-02-2017-2096
|View full text |Cite
|
Sign up to set email alerts
|

Are attractive reviewers more persuasive? Examining the role of physical attractiveness in online reviews

Abstract: Purpose While online reviews are of paramount importance in brand evaluations and purchase decisions, the impact of a reviewer’s attractiveness is not well understood. To bridge that gap, this paper aims to explore how physical attractiveness cues through profile photos influence customers’ brand evaluations. Design/methodology/approach The first study assesses the impact of attractiveness and review valence on brand evaluations. The authors used an experimental design and tested the model with an ANCOVA. St… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 88 publications
0
21
0
Order By: Relevance
“…Consumer skepticism toward online reviews is tied to message content and style and review extremity and valence (Filieri, 2016). The profile photo/ attractiveness of the reviewer (Ozanne et al, 2019), linguistic style and reported experience of the reviewers reduce the socialpsychological distance between the reviewer and the potential consumer, reducing consumer skepticism toward the online reviewer (Hern andez-Ortega, 2018). Review characteristics such as positivity, involvement and sociability can generate skepticism among readers (Banerjee et al, 2017).…”
Section: Skepticism and Reliance On Online Reviewsmentioning
confidence: 99%
See 2 more Smart Citations
“…Consumer skepticism toward online reviews is tied to message content and style and review extremity and valence (Filieri, 2016). The profile photo/ attractiveness of the reviewer (Ozanne et al, 2019), linguistic style and reported experience of the reviewers reduce the socialpsychological distance between the reviewer and the potential consumer, reducing consumer skepticism toward the online reviewer (Hern andez-Ortega, 2018). Review characteristics such as positivity, involvement and sociability can generate skepticism among readers (Banerjee et al, 2017).…”
Section: Skepticism and Reliance On Online Reviewsmentioning
confidence: 99%
“…Online reviews are becoming a critical consumption decision factor. Recent research suggests electronic word of mouth is perceived as less misleading and more specific and trustworthy than traditional marketing communications (Ngarmwongnoi et al, 2020;Ozanne et al, 2019;Rynarzewska, 2019). The Pew Research Center finds that 82% of American adults read online reviews before purchasing any item and that almost half of the American adults believe it is hard to tell if online reviews are truthful and unbiased (Smith and Anderson, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Attractiveness is defined by many researchers as a combination of similarity, familiarity, and likability of credibility sources (Maddux & Rogers, 1980;Steadman, 1969). Numerous studies have shown that celebrity's attractiveness has a positive effect on brand image, attitudes toward the brand and purchasing intention (Joseph, 1982;Mello, Garcia-Marques, Briñol, Cancela, & Petty, 2020;Ozanne, Liu, & Mattila, 2019); and it also becomes more favorable if the attractiveness of the endorser has increased (Kamins, 1990). Besides, attractiveness is not only about appearance but also requires the spiritual skills, personality, lifestyle, and talent of celebrities (Erdogan, 1999).…”
Section: Source Credibility Theory (Sc)mentioning
confidence: 99%
“…In 1920, Edward Thorndike (1920) observed that military commanding officers’ ratings of subordinates’ performance changed after they interacted with their subordinates. More recently, the halo effect has been documented in a variety of contexts such as ratings of students (e.g., Malouff & Thorsteinsson, 2016), teachers (e.g., Keeley et al, 2013), employees (e.g., Viswesvaran et al, 2005), managers (e.g., Mathisen et al, 2011), politicians (e.g., Babad et al, 2012), online reviewers (e.g., Ozanne et al, 2019), and multiattribute objects such as websites (Kwak et al, 2019), resulting in biased perceptions of characteristics like success, competence, intelligence, and expertise. Given the apparent pervasiveness of this interpersonal bias, evaluation of the therapeutic encounter may also be susceptible.…”
mentioning
confidence: 99%